Reading Carey Between the Lines - Pauly, John (Explorations in Media Ecology, 2006)
Abstract James Carey’s approach to media studies was far-ranging and interdisciplinary. His writings demonstrate the influence of several intellectual traditions, including pragmatism, British cultural studies, American studies, and Catholic social thought. Although his earlier work addressed general issues of media systems and culture, Carey later wrote frequently about journalism, in part because of his interest in the problems of public life in democratic societies, in part because journalism illustrated his commitment to media theory as a historically and socially situated cultural practice.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9lbWUuNS4yLjE1NV8x